THEORETICAL CALCULATION OF ELECTRON TRANSFER COEFFICIENT FOR PREDICTING THE FLOW OF ELECTRONS BY PM3, USING 20 AMINO ACIDS AND NICOTINE - Perez, Manuel Gonzalez; Barrera, Francisco Antonio Garcia; Diaz, Juan Francisco Mendez; Torres, Maykel Gonzalez; Oglesby, Juan Manuel Lopez (European Scientific Journal, ESJ, 2014)
In this work, an Electron Transfer Coefficient (ETC) it derived for various chemical species to help predict the flow of electrons in amino acidnicotine interactions. The quantum method "Semi-Empirical Parameterized Models Number 3" (SE-PM3) was set to calculate the variables HOMOLUMO, the Gap Band (BG) and the Electrostatic Potential (EP) of 20 Amino Acids (AA) and Nicotine. In conclusion, the electrons need more energy to jump their BG when the ETC is large; thus, the electrons flow toward the lower value of the ETC. Tryptophan has an ETC = 19.1, Isoleucine has an ETC = 54.573, and Nicotine has an ETC = 40.873. The ETC of nicotine is in the middle of the ETC of 20 different AA.